REPORT ON ACTIVITY OF EDITORIAL BOARD OF "RATIONAL PHARMACOT HERAPY IN CARDIOLOGY" IN 2014 - M. I. Smirnova (Столичная издательская компания, 2015)
Report on activity of editorial board of "Rational Pharmacot herapy in Cardiology" in 2014.